Pendekatan Konseling Islam dalam Mengatasi Stres Akademik Siswa - Koto, Nyolanda Wulandari; Lahmuddin, Lahmuddin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyse the implementation of Islamic counselling approaches to overcome academic stress and understand the spiritual changes experienced by students during counselling. A qualitative descriptive approach was employed for this research, involving 10 students who exhibited symptoms of academic stress. Data were collected through observation, in-depth interviews and documentation. The findings revealed that five students practised tahajjud prayer therapy, two routinely read the Qur'an and three practised dhikr and prayer as religious coping mechanisms. These approaches contributed to reducing anxiety, improving emotional stability, strengthening self-confidence and developing adaptive coping strategies. Students also underwent spiritual development, interpreting academic pressure as a test of life that could be overcome through patience, effort, and reliance on Allah SWT. The study concludes that Islamic counselling is effective in helping students manage academic stress by integrating psychological and spiritual approaches within the madrasah environment.